(untitled) (The Pakistan Development Review, 1997)
The Korean development experience presents a successful transition from ‘learning-by-doing’ to ‘learning-by-research’. In his book, Professor Kim explores the dynamics of the Korean companies’ technological learning acquisition for technological capability. His main conclusion is that in spite of the favourable impact of public policy and cultural environment, private industry made Korea’s ambitious development goals a reality.